On the accelerants of non-self-adjoint Dirac operators - Puyda, D. V.; Mykytyuk, Ya. V. (Methods of Functional Analysis and Topology, 2014)
We prove that there is a homeomorphism between the space of accelerants and the space of potentials of non-self-adjoint Dirac operators on a finite interval.